Habitat : New and Selected Poems, 1965-2005 - Galvin, Brendan (Book collections on Project MUSE., 2005)
"Habitat, Galvin's fourteenth poetry book, combines eighteen new works with lyric pieces from the past forty years - including two book-length narratives, Wampanoag Traveler and Saints in Their Ox-Hide Boat. Galvin intimately conveys his landscapes, birds and animals, people, and weather. By elevating the commonplace to the crucial, he takes his readers very far from the familiar."--Jacket